GRAIN YIELD AND YIELD COMPONENTS BY SOYBEAN CANOPY STRATUM IN RESPONSE TO PLANT ARRANGEMENT AND WATER AVAILABILITY - RAMBO, Lisandro; COSTA, José Antonio; PIRES, João Leonardo Fernandes; PARCIANELLO, Geovano; FERREIRA, Felipe Gutheil (Scientia Agraria, 2002)
Plant arrangement that allow better plant distribuition in the area results in larger grain yield. This increase might be the result of diferential contribution of canopy strata for yield determination. The experiment was performed at Agronomic Experimental Estation of the Universidade Federal do Rio Grande do Sul, in Eldorado do Sul, Rio Grande do Sul, Brazil, in the 2000/01 growing season. The objectives were to evaluate grain yield and yield components by stratum of soybean canopy in different plant arrangements, under two water availability. Tested cultivar was BRS 137 (early, determinate), in no-till planting. Treatments arrangements were split-splitplot randomized complete-block design, with four replications. Water availability (irrigate and no irrigated), row spacing (20 and 40 cm) and population levels (20, 30 and 40 plants.m-2) were tested. Grain yield and yield components, by soybean canopy stratum, were determined in samples of ten plants, in sequence in the row, in each sub-subplot. Grain yield was incresead by irrigation and was detected interaction between row spacing and plant population. Plant arrangememnt of 20 cm row spacing and population of 20 plants.m-2 resulted in greater grain yield. There was a linear decrease in grain yield with the increase in population, with reduced row spacing (20 cm). The same was also noticed at medium and bottom stratum. The upper and medium soybean canopy stratum present higher contribution to grain yield, due major number of fertil pods. The row spacing and plant population reduction modify positively the medium and bottom canopy estratum contribution to grain yield.